Highly Improved Thermal Properties of Hydroxyl‐Containing Polymers via Modification by Benzoxazine Groups. Issue 14 (17th July 2013) - Chiou, Kevin; Hollanger, Erin; Agag, Tarek; Ishida, Hatsuo
Abstract Isocyanate functional benzoxazine (NCO‐4HBA‐a) is used for coupling with hydroxyl‐group‐containing molecules. Glycerol is used in a model reaction to study the urethane bonds formed between the NCO‐4HBA‐a and the glycerol's hydroxyl groups. The model supports a reaction between NCO‐4HBA‐a and poly(vinyl alcohol) (PVA), which leads to an improved char yield, determined by thermogravimetric analysis. Glycerol‐based benzoxazine is also an attractive benzoxazine synthesized from the products of biofuel production. Upon functionalization with benzoxazine and subsequent thermal treatment, the hydroxyl‐containing polymer gains thermal stability shown by improved char yield of polybenzoxazine cross‐linked PVA.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>